Three-Dimensional Endoscopic Magnification for Treatment of Thoracic Spinal Dural Arteriovenous Fistulas: Technical Note. Issue 3 (25th July 2017) - Weil, Alexander G; Obaid, Sami; Chaalala, Chiraz; Shedid, Daniel; Magro, Elsa; Seizeur, Romuald; Bojanowski, Michel W
Abstract: BACKGROUND: Treatment of thoracic spinal dural arteriovenous fistulas (DAVFs) by microsurgery has recently been approached using minimally invasive spine surgery (MISS). The advantages of such an approach are offset by difficult maneuverability within the tubular retractor and by the creation of "tunnel vision" with reduced luminosity to a remote surgical target. OBJECTIVE: To demonstrate how the pitfalls of MISS can be addressed by applying 3-D endoscopy to the minimally invasive approach of spinal DAVFs. METHODS: We present 2 cases of symptomatic thoracic DAVFs that were not amenable to endovascular treatment. The DAVFs were excluded solely via a minimally invasive approach using a 3-D endoscope. RESULTS: Two patients underwent exclusion of a DAVF following laminotomy, one through a midline 5-cm incision and the other through a paramedian 3-cm incision using minimally invasive nonexpandable tubular retractors. The dura opening, intradural exploration, fistula exclusion, and closure were performed solely under endoscopic 3-D magnification. No incidents were recorded and the postoperative course was marked by clinical improvement. Postoperative imaging confirmed the exclusion of the DAVFs. Anatomical details are exposed using intraoperative videos. CONCLUSION: When approaching DAVFs via MISS, replacing the microscope with the endoscope remedies the limitations related to the "tunnel vision" created by the tubular retractor, but at the expense of losing binocular vision. We show that the 3-D endoscope resolves this latter limitation and provides an interesting option for the exclusion of spinal DAVFs.